2002
DOI: 10.1001/archopht.120.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Performance of Bifocal and Multifocal Intraocular Lenses in a Model Eye

Abstract: To compare the optical properties of bifocal diffractive and multifocal refractive intraocular lenses. Methods: A model eye with a pupil 4.5 mm in diameter was used to determine the point spread function (PSF) of the distance focus and near focus of a diffractive bifocal intraocular lens (IOL) (model 811E; Pharmacia Inc, Columbus, Ohio) and of a refractive multifocal IOL (model SA40N; Allergan Optical Inc, Irvine, Calif) to compare them with PSFs of foci of corresponding monofocal lenses. For interpreting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 29 publications
2
48
0
4
Order By: Relevance
“…Also chromatic aberration is expected to be equivalent to that of a real eye because of the similar constringence of PMMA and corneal stroma (57.2 and 56, respectively). Incidentally, the PMMA cornea of the artificial eye developed by Pieh et al, 4 exactly reproducing the curvatures of the Gullstrand eye model, has a power in defect by 4% relative to the Gullstrand power as a result of the different refractive index.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Also chromatic aberration is expected to be equivalent to that of a real eye because of the similar constringence of PMMA and corneal stroma (57.2 and 56, respectively). Incidentally, the PMMA cornea of the artificial eye developed by Pieh et al, 4 exactly reproducing the curvatures of the Gullstrand eye model, has a power in defect by 4% relative to the Gullstrand power as a result of the different refractive index.…”
Section: Discussionmentioning
confidence: 97%
“…This image can then be analyzed with standard optical methods to recover PSF, MTF, or aberration coefficients for different pupil sizes, as done in other studies. 1,2,4,5,8,30 All these quantities completely characterize the linear optical behavior of the eye model, thus allowing immediate and homogeneous comparison of IOLs with equal dioptric power and different material or design features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to this, some of these lenses have an aspheric base design that can be advantageous in comparison the conventional spherical one. There is a great interest to determine either in a test bench [43], [44] or in clinical studies [45], [46] the conditions and the degree to which the aspheric design in apodized diffractive multifocal IOLs might be advantageous versus a conventional spherical design, particularly when some studies have shown little or no benefit of aspheric IOLs with small pupils [47, [48]. For the assessment of the optical performance of multifocal IOLs, the common metrics (point spread function, modulation transfer function, and visual acuity) have to be measured [38], [49][50][51][52] and also its behaviour in terms of the energy balance between the distance an near images and its variation with the pupil diameter.…”
Section: Model Eyes For Iol Testingmentioning
confidence: 99%
“…Negish et al [2] and Pieh et al [3] constructed an artificial eye with a man-made cornea, an IOL, a charge-coupled device (CCD) camera, and filled water to simulate aqueous and vitreous. Then the retinal image quality with a monofocal or multifocal IOL was evaluated by the images acquired with CCD camera.…”
Section: Introductionmentioning
confidence: 99%